PEMBINAAN AKTIVITAS KEAGAMAAN PADA ANAK DI TK/TPA DUSUN BONTOMANAI DESA POLEWALI - syarifuddin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2024)
This development can also be interpreted as an effort from education, both formal and non-formal, which is carried out consciously, planned, directed and responsible in increasing the achievement of Indonesia's educational goals in general, namely to make the nation's life smarter. This Kindergarten/TPA is a place for every child who wants to learn to read, write and understand the holy book Al-Qur'an from an early age in order to create children with Koranic morals who make the Al-Qur'an their life guide from the start. early. The aim of establishing a Kindergarten/TPA in Polewali Village, Bontomanai Hamlet by KKN-P UIAD is to eradicate Al-Qur'an illiteracy, introduce basic Arabic, improve memorization of short surahs, and introduce that studying the Al-Qur'an is not boring by inserting games into learning activities